Patient-Centered Evaluation of Phlebotomy Services: A Quantitative Analysis from a Clinical Setting - ullah, irfan; Kanwal , Aisha; Ali Shah, Syed Hammad; Khattak, Toheed Zaman; Ullah, Dildar (ADVANCES IN BASIC MEDICAL SCIENCES, 2026)
OBJECTIVE: The main aim of the present study is to assess the satisfaction among patients with phlebotomy services in a tertiary care hospital with a standardized questionnaire to identify the key factors contributing to dissatisfaction and execute the relevant Corrective and Preventive Actions (CAPA). METHODOLOGY: A descriptive cross-sectional (survey-based) study was conducted at a tertiary care hospital in Peshawar, Pakistan, from June to December 2024. A total of 100 patients were randomly selected to participate. Data were collected using a self-developed questionnaire, prepared in both Urdu and English, comprising twelve items rated on a Likert scale. Statistical analysis was performed using SPSS version 26.0. RESULTS: 93% of respondents reported satisfaction regarding the phlebotomy services. Approximately thirty percent (30.0%) of the participants reported excellent satisfaction with the phlebotomy services, but the majority, 40.5%, deemed them good. Furthermore, 23.5% saw the services as indifferent, 4% as dissatisfied, and 3% as severely dissatisfied. The highest satisfaction rating was achieved for the comfort level during the blood draw, while the lowest satisfaction rate was associated with the total waiting time in the phlebotomy department and the cleanliness of the phlebotomy space. CONCLUSION: Despite overall patient satisfaction, several areas need our attention, including the waiting time for phlebotomy procedures, inadequate seating arrangements, sample collecting practices, and understanding of standard precautions. Suitable corrective and preventative measures are implemented to address issues.